POROUS TITANIUM - AN ENHANCED SUPPORT FOR HUMAN OSTEOBLASTS AFTER ANODIZATION AND c-RGD IMMOBILIZATION - SALANTIU, Ana-Maria; SORITAU, Olga; DIRZU, Noemi; POPA, Florin; MUREŞAN, Liana Maria; POPESCU, Violeta; PASCUTA, Petru; POPA, Cătălin (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Porous titanium is the material of choice for hard tissue implants but an enhanced osseointegration can be achieved only through subsequent surface conditioning. In this work, we aimed to study the effect of both surface conditioning and immobilization of cyclic Arg-Gly-Asp (RGD) peptide onto two types of porous titanium samples designed for endosseous applications and obtained by Powder Metallurgy (PM) in view of osteoblast cells attachment and proliferation. Cyclic RGD peptide was chosen as bioactive target and was covalently immobilized on anodized PM porous titanium. The samples, formerly pressed with 200 or 400 MPa and sintered at 1100°C in vacuum, were first anodized using a constant voltage of 2V for 1 hour with 0.25 M sulphuric acid to enhance the thickness of titanium oxide layer. An intermediary aminoalkylsilane molecule (APTES) was then covalently linked to the oxide layer, followed by the covalent binding of cyclic RGD peptide to the free terminal NH2 groups using polyethylenglycol diglycidyl ether (PEGDE) as coupling agent. The samples were characterized by micro CT, X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR). Anodized titanium samples display anatase and rutile on the surface and, after functionalization, two important amide characteristic regions, confirming the presence of cyclic RGD peptide. Cells seeded on samples pressed with 400 MPa, anodized and c-RGD immobilized, displayed a more flattened shape and a more obvious tendency of spreading into pores.